The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.5551/jat.48330
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein Subfractions and Glucose Homeostasis in Prediabetes and Diabetes in Taiwan

Abstract: Aims: Prediabetes and diabetes are associated with increased insulin resistance and decreased insulin production, dyslipidemia, and increased cardiovascular disease (CVD) risk. Our goals were to assess lipoprotein subfractions using novel assays in such subjects.Methods: Fasting normal, prediabetic, and diabetic Taiwanese men and women (n = 2,049) had their serum glucose, glycosylated hemoglobin, insulin, total cholesterol (TC), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), HDL3-C, apolipop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 51 publications
2
16
0
Order By: Relevance
“…Therefore, it is apparent that the measurement of LDLC quantifies the cholesterol content of LDL particles but does not take into account the vast heterogeneity of LDL particles among individuals, and the use of LDLC to evaluate cholesterol-related cardiovascular risk may actually underestimate future risk in individuals who have a high level of circulating sdLDLC. Except for the atherogenic role of sdLDLC, it was also found that sdLDLC levels were strongly associated with atherosclerotic risk markers such as inflammation, thrombosis, hematologic markers 26 ) , and prediabetes 27 ) , which was further demonstrated in our study where sdLDLC levels were significantly correlated with hs-CRP and fasting blood glucose in the general population. Taking all these findings into account, the measurement of sdLDLC may therefore help clinicians to reclassify individuals thought to be at low risk into the high-risk category, for early intervention.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, it is apparent that the measurement of LDLC quantifies the cholesterol content of LDL particles but does not take into account the vast heterogeneity of LDL particles among individuals, and the use of LDLC to evaluate cholesterol-related cardiovascular risk may actually underestimate future risk in individuals who have a high level of circulating sdLDLC. Except for the atherogenic role of sdLDLC, it was also found that sdLDLC levels were strongly associated with atherosclerotic risk markers such as inflammation, thrombosis, hematologic markers 26 ) , and prediabetes 27 ) , which was further demonstrated in our study where sdLDLC levels were significantly correlated with hs-CRP and fasting blood glucose in the general population. Taking all these findings into account, the measurement of sdLDLC may therefore help clinicians to reclassify individuals thought to be at low risk into the high-risk category, for early intervention.…”
Section: Discussionsupporting
confidence: 82%
“…However, routine lipid measures may not well reflect the compositional changes of lipid parameters in DM and Pre-DM patients. For example, no significant increase in LDL-C levels was found in some DM and Pre-DM patients [16]. In patients with metabolic disorder, the increase in very low-density lipoprotein (VLDL) particles could initiate a sequence of hydrolysis process and result in higher plasma sdLDL levels [6].…”
Section: Discussionmentioning
confidence: 99%
“…In hyperglycemic status, the HL-mediated pathway is more active [6]. Thus, the plasma level of sdLDL is significantly elevated in pre-diabetes (Pre-DM) and DM individuals [13,16]. Furthermore, sdLDL is more susceptible to glycation than lbLDL, which may increase its atherogenicity [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, even after intensive lowering of LDL-C, the absolute risk of events in DM patients is still higher than that in non-diabetic patients. Hypertriglyceridemia is the main feature of lipid disorder in DM and Pre-DM and could induce a sequence of compositional changes for lipid parameters including low HDL-cholesterol and type B pattern of LDL distribution [32,33]. Despite the undisputable causal role of elevated LDL-C in patients with DM [34], TG-enriched lipoproteins were significantly elevated while plasma levels of LDL-C were usually within the normal range [12].…”
Section: Discussionmentioning
confidence: 99%